Knowledge about antibiotics and antibiotic resistance among health-related students in a Saudi University - Zafar Akbar; Nahed Alquwez; Abdulellah Alsolais; Suhas Kaniyarakkal Thazha; Mohammad Dabeer Ahmad; Jonas Preposi Cruz (Journal of Infection in Developing Countries)
Introduction: Antibiotic resistance is a threat to public health and safety globally. The inadequate undergraduate education on antibiotic stewardship may contribute to the clinical malpractice of antibiotics, causing serious consequences toward patient health. Thus, this study aimed to evaluate the knowledge of future healthcare workers in Saudi Arabia on antibiotics, antibiotic use, and antibiotic resistance. The factors influencing the students’ knowledge were also determined.